MODL-25. REPLICATION REPAIR DEFICIENT MOUSE MODELS PROVIDE INSIGHT ON HYPERMUTANT BRAIN TUMOURS, MECHANISMS OF IMMUNE EVASION, AND COMBINATORIAL IMMUNOTHERAPY. (4th December 2020) - Galati, Melissa; Li, Li; Sudhaman, Sumedha; Lipman, Tatiana; Stengs, Lucie; Elshaer, Dana; Bridge, Taylor; Semenova, Dar'ya; Edwards, Melissa; Hodel, Karl; Forster, Victoria J; Nunes, Nuno M; et al.
Abstract: Replication repair deficiency (RRD) is the leading cause of hypermutant brain tumours in children. RRD is caused by defects in one of four mismatch repair (MMR) genes and mutations in POLE or POLD1 . Such tumours are resistant to common therapeutic agents and animal models are needed to study RRD in vivo and test novel therapies like immune checkpoint inhibitors (ICIs). To model RRD brain tumours specifically, we engineered a Pole mutant mouse model harbouring the S459F mutation ( Pole S459F ). We combined Pole S459F mice with conditional Msh2 knockout ( Msh2 LoxP ) and Nestin-cre mice. All Nestin-cre + Msh2 LoxP/LoxP Pole S459F/+ mice rapidly succumbed to posterior fossa brain tumours between 8.6 and 12.4 weeks. Importantly, tumours exhibited hallmark "ultrahypermutation" (~350 mutations/Mb) and the corresponding signatures characteristic of human combined MMR and POLE -proofreading glioblastoma. Interestingly, Nestin-cre + Msh2 LoxP/LoxP Pole S459F/S459F mice failed to establish normal cerebella, suggesting such mutational loads may not support normal brain development. Furthermore, OLIG2-cre + Msh2 LoxP/LoxP Pole S459F/+ mice failed to develop tumors. Tumors transplanted into syngeneic vs immunocompromised animals egrafted well orthotopically in the mouse hindbrain but significantly less efficiently when engrafted subcutaneously. Furthermore, immunocompromised and subcutaneous tumors revealed striking differences in mutational burden and clonal architecture, suggestive of nonautonomous immunoediting. Finally, anti-PD1 was sufficient to treat subcutaneously engrafted tumors in immunocompetent animals. This first mouse model of immunocompetent, hypermutant brain tumors can be used to uncover unique characteristics of RRD tumour evolution and allow for immune based therapeutic preclinical testing. Experiments to assess combinational ICIs and other therapeutic interventions in orthotopically transplanted tumors will also be presented.